Synthetic studies toward tetrapetalone A: attempted palladium π-allyl cascades toward a fused tricyclic intermediate. Issue 26 (30th June 2016) - Dhanjee, Heemal H.; Haley, Matthew W.; McMahon, Travis C.; Buergler, Jonas F.; Howell, Jennifer M.; Kobayashi, Yutaka; Fujiwara, Koichi; Wood, John L.
Abstract: Efforts to install the core azepine ring in tetrapetalone A via a palladium π-allyl cascade reaction failed due to competing pathways that included an unexpected and interesting TMM-like cycloaddition reaction that delivers a complex tricyclic ring system. Graphical abstract: